Investment horizon effect on asset allocation between value and growth strategies - In, Francis; Kim, Sangbae; Gençay, Ramazan (Economic modelling, 2011)
How does the optimal risk exposure of assets change as their investment horizons increase? Does this impact investment portfolio decision-making, in particular, optimal asset allocation between value and growth strategies over various investment horizons? This paper adopts a new approach to address these questions by examining portfolio allocation between value and growth stocks over various investment horizons. This new approach is based on wavelet analysis, which decomposes the returns of a particular investment strategy across multiple investment horizons. The key empirical results show that the success of pursuing the value strategy (short-selling growth stocks and going long on value stocks) is impacted by the approach used to classify value and growth stock returns. We explore two common alternatives: Fama–French versus Standard & Poor's (S&P) 500/Barra portfolios. The results using Fama–French portfolios show that as the investment horizon increases, the optimal mean allocation of investors tilts heavily away from growth stocks, particularly for lower and moderate levels of risk aversion. Interestingly, for S&P 500/Barra portfolios the allocation weights between value and growth do not vary much. ► We model asset allocation between value and growth strategies using wavelet analysis. ► We examine the changes of the optimal allocation weight over various horizons. ► We explore two common alternatives: Fama-French versus S&P 500/Barra portfolios. ► The success of the value strategy depend on the classifying approach.